Influence of ancient armies’ military arts on forms of combat order of the Interior Troops units - Varakuta, V. P.; Glazkov О. V. (Honor and Law, 2019)
The influence of ancient armies’ military arts on the selection of forms of combat order, Troops of the Interior units, Ukraine, depending on the assigned combat-routine mission is shown and defined.